Lingua franca as the economic category - Хоменко, О. В. (Pedagogy of Higher and Secondary Education, 2013)
Khomenko O. Lingua franca as the economic category. The paper dwells on the reciprocal impact of economy and lingua franca in today’s globalized world. Besides the author underscores the legitimacy of attributing the lingua franca to the economic category.